2005
DOI: 10.1007/s10964-005-7261-0
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Stereotypes About the Rich and Poor: Age, Race, and Family Income Differences in Beliefs

Abstract: African American and European American 4th, 6th, and 8th graders rated the competence of rich and poor children in academics (i.e., math, science, reading, writing, school grades, smartness), sports, and music. In contrast to middle school students, 4th graders favored the rich in all 3 domains. Youth of both races reported that the rich were more competent in academics than the poor; these beliefs were especially pronounced among Black youth. White, older, and more affluent students favored the poor in sports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 32 publications
(42 reference statements)
3
59
0
1
Order By: Relevance
“…Hence, ecology stereotypes are not derivative of wealth stereotypes; they are applied to both wealthy and poor individuals. These findings also suggest that ecology stereotypes are not simply stereotypes about the socioeconomic status or social classes of individuals (23). Indeed, unlike approaches focusing on specific historical and sociological conditions that shape stereotypes of the economically disadvantaged (24), our approach suggests that similar ecology-driven stereotypes are likely to exist across societies, a point we address in Discussion.…”
Section: Significancementioning
confidence: 82%
“…Hence, ecology stereotypes are not derivative of wealth stereotypes; they are applied to both wealthy and poor individuals. These findings also suggest that ecology stereotypes are not simply stereotypes about the socioeconomic status or social classes of individuals (23). Indeed, unlike approaches focusing on specific historical and sociological conditions that shape stereotypes of the economically disadvantaged (24), our approach suggests that similar ecology-driven stereotypes are likely to exist across societies, a point we address in Discussion.…”
Section: Significancementioning
confidence: 82%
“…As a consequence, welfare recipients sense that society sees them as criminals, "milking the system. " (Underlid, 2005) Although the content of the stereotype of poor people as outlined in earlier research primarily originates from North American studies (as in Bullock, 1999;Cozzarelli et al, 2001;Gilmore & Harris, 2008;Henry, Reyna, & Weiner, 2004;Kluegel & Smith, 1986;Woods et al, 2005), researchers have identified similar stereotype content across post-communist countries, such as Hungary and Russia, where the acceptance of inequality and poverty seems to be lower than in the United States (Kreidl, 2000).…”
Section: Stereotypes Of the Poormentioning
confidence: 99%
“…Similar examples are extensive and widespread: The stereotype of the poor includes unfavorable individual properties, such as having low intelligence, being lazy, and not being interested in self-improvement (see e.g. Bullock, 1995;Cozzarelli, Wilkinson, & Tagler, 2001;Kreidl, 2000;Lott, 2002;Woods, Kurtz-Costes, & Rowley, 2005). Poor individuals are often held to have themselves to blame (Bolitho, Carr, & Fletcher, 2007;Kluegel & Smith, 1986).…”
Section: Stereotypes Of the Poormentioning
confidence: 99%
“…Such stereotypes are especially important in the transition to adolescence, when youth experience rapid physical, social and cognitive changes (Woods, Kurtz-Costes, & Rowley, 2005).…”
Section: Social Images: Definitions and Effectsmentioning
confidence: 99%
“…Some studies demonstrate how youth in care are perceived as problematic, different, marginal, needy, abandoned, weak, or poorly qualified (Arpini, 2003) and having low academic competence (Woods et al, 2005). Such perceptions also contain dimensions such as sadness, poverty, loneliness, abandoned and rootless and negative features expressed in terms of appearance (e.g., dirty) and behaviour (e.g., insolent, hostile) (Kuznetsova, 2005).…”
Section: Social Images In the Residential Care Contextmentioning
confidence: 99%